Use of microalgae and potential nanotechnological application: a review - Fonseca, Elisandra da Silva Pena da; Santini, Jéssica Cristine Viera Machado; de Sousa Filho, Walter Paixão; Bortoluzzi, Luisa Donato; Vieira, Wanessa de Carvalho; de Souza, Diego; Fernandes, Liana da Silva; Sagrillo, Michele Rorato (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Microalgae are eukaryotic and unicellular microorganisms of simple structure, colonial that need for their growth and reproduction, light, water, carbon dioxide and inorganic nutrients. Demonstrate commercial interest due to a biomass rich in bioactive substances, such as pigments, lipids, polyunsaturated fatty acids, carbohydrates, proteins, and vitamins. Among these substances, Chlorella microalgae oil contains lipids with a wide range of interesting properties. In this context, the present review aims to demonstrate the potential and applications of microalgae, mainly of the Chlorella species, as well as the methods and conditions of cultivation, the chemical composition, and its relationship with nanotechnology. The data for this review were obtained from a search in the main databases such as Scielo, Scopus and Science Direct, without restriction to the period of publication, using following descriptors: microalgae, Chlorella, biomass, oil, application, nanotechnology and their combinations. These microorganisms, as they are easy to cultivate and rapidly proliferate, are gaining ground in the area of new technologies involving species of the Chlorella type, which has several applications, including in the nutraceutical and cosmetics area, guaranteeing products with quality, efficacy and biodegradable assets.